The scope and infringement of patents claiming strains of bacteria. Issue 8 (17th August 2022) - MacLeod, Ian
Abstract : Increasing numbers of patents directed to bacteria and bacterial products are being filed and granted, many of which claim specific deposited strains of bacteria. However, there remains significant uncertainty regarding exactly what scope patent claims limited to deposited strains might have. A claim limited to a specific deposited strain could be interpreted extremely narrowly, extending only to descendants of that deposit. However, a review of the available guidance from courts across the globe suggests that in practice such claims are likely to be infringed by competitor products. The commercial value of patent claims to bacteria depends on the regulatory and competitive landscape, and can be strengthened by appropriate details in patent applications.